Energy-Efficient Transmission Based on Direct Links: Toward Secure Cooperative Internet of Things - Shang, Xiaohui; Liu, Aijun; Wang, Yida; Xie, Qing; Wang, Yong (Wireless Communications and Mobile Computing, 2018)
In this paper, the secure uplink transmission scenario in Internet of Things (IoT) applications is investigated, where one of multiple sensors communicates with the controller aided by the cooperative relay. Firstly, by considering the direct link, an energy-efficient transmission scheme (EET) is proposed, which can be suitable for the resource-constrained devices and applications in IoT communication. Moreover, the secrecy outage probability (SOP) and secure energy efficiency (SEE) of different transmission strategies are derived, which contributes to the design of energy-efficient secure transmission. Finally, simulation results demonstrate that EET outperforms other transmission protocols in terms of SEE in most situations. To improve the secrecy performance and energy efficiency of the IoT deployment, EET can be adopted as an effective additional strategy in practical applications.